The relationship between loss, macroeconomic condition and conservatism - Abdullah Atqa, Asna; Mohd Saleh, Norman; Ahmad, Azlina; Abdul Latiff, Radziah (Growing Science, 2019)
This study is motivated by the high frequency of loss occurrence since late 1990s among Malaysian public listed firms, and the conflicting findings of the impact of the macroeconomic conditions and firm-specific attributes on different measures of earnings quality. In addition, this study examines the impact of firms’ specific attributes on earnings quality using a better established theory, known as the life-cycle hypothesis. The objectives of this study are; (1) to examine the relationship between firms’ loss condition on conservatism as an earnings quality measure as well as the moderation of macroeconomic condition on the relationship and (2) to examine the relationship between life-cycle stages and conditional conservatism. Samples for the study are companies listed on Bursa Malaysia from 1995 to 2010. Using the C_Score measure of conservatism as the dependent variable, firms with loss condition, have been found to be significantly more conservative than profit firms. In addition, macroeconomic condition, strengthen the relationship between loss and conservatism when the results indicate that loss firms undergoing economic crisis are significantly more conservative than loss firms under normal economic condition. Incorporating the firms’ life-cycle stages, the study found that growth firms signal fewer losses than mature firms, thus accepting the set hypothesis. Implication of this study is that ignorance of these issues could lead to significantly misleading interpretation of earnings quality.